Left Atrial Volume versus Coronary Artery Calcium Score in Patients on Peritoneal Dialysis: An Observational Study - Reis, Fabricio Moreira; Ferrari, Eduarda Baccarin; Reis, Nayrana Soares do Carmo; Costa, Fabiana Lourenço; Morimoto, Paula Naomi; Maurício, Alejandra Del Carmen Villanueva [UNESP]; Hueb, João Carlos; Bazan, Rodrigo; Banin, Vanessa Burgugi; Barretti, Pasqual; Martin, Luis Cuadrado; Bazan, Silmeia Garcia Zanati (MDPI, 2024)
Background: The coronary artery calcium score and left atrial volume have been shown to predict the incidence of acute myocardial infarction and death from cardiovascular disease in patients undergoing peritoneal dialysis. However, the association between these factors has not been well-established. Methods: This cross-sectional, prospective, single-center study was conducted on patients undergoing outpatient peritoneal dialysis, who were followed up at a university hospital between March 2018 and August 2019. The coronary artery calcium score was calculated based on cardiovascular computed tomography findings. The score was "positive" when it was ≥100 Agatston and "negative" when it was <100 Agatston. The left atrial volume was obtained using the biplane disc method at the end of the left ventricular systole, and then it was indexed to the body surface. Results: Forty-four patients were evaluated. They had an age [mean (range)] of 56 (43-65) years and had been on dialysis therapy for 11.7 (6.8-25.4) months. Univariate analysis revealed a relationship between the coronary artery calcium score and left atrial volume index and the following variables: age, diabetes, overhydration, pulse wave velocity, E/A ratio, and left ventricular mass index. In multivariate logistic regression analysis, only the left atrial volume index was independently associated with a positive coronary artery calcium score. Conclusions: The left atrial volume index was associated with a positive coronary artery calcium score in patients on peritoneal dialysis, regardless of other factors. It may be a useful risk marker for coronary artery disease in this population.